Pesticides in sediments of the Ebro River Delta cultivated area (NE Spain): Occurrence and risk assessment for aquatic organisms. (15th July 2022) - Peris, A.; Barbieri, M.V.; Postigo, C.; Rambla-Alegre, M.; López de Alda, M.; Eljarrat, E.
Abstract: Intense agricultural activities are performed in the Ebro River Delta (NE Spain) with extensive use of pesticides. Medium to highly polar pesticides have not been studied intensively in sediments despite its larger use in the recent years. This work aimed at assessing the occurrence of 69 pesticides, including medium to highly polar compounds, in sediments collected from drainage and irrigation channels of the Ebro River Delta during the main rice growing season. In addition, an environmental risk assessment was performed to evaluate the potential adverse effects to sediment-dwelling organisms with the risk quotient approach. A total of 24 pesticides were detected in sediments with bentazone and cypermethrin exhibiting high detection frequencies (79%) as well as high mean concentration levels (61.9 and 81.8 ng g −1 dw, respectively). Overall, the Alfacs bay, in the South of the delta, presented higher pesticide contamination than the Fangar bay, in the North. A similar pesticide distribution profile was observed in both bays, with oxadiazoles, organochlorines, pyrethroids, benzothiazinones and organophosphates as major, predominant classes. The presence of oxadiazon, pendimethalin and thifensulfuron methyl in the sediments may pose a moderate risk to sediment-dwelling organisms while bentazone, chlorpyrifos, and cypermethrin exhibited a potential high risk. Thus, the importance of the inclusion of medium to highly polar pesticides in the analysis of sediments is emphasized since some polar pesticides such as bentazone, imidacloprid, and thifensulfuron-methyl have been detected at concentrations that may pose a risk to aquatic organisms. Moreover, the co-occurrence of pesticides may potentially pose a high risk to sediment-dwelling organisms in 13 out of the 14 investigated locations. Finally, it could be concluded that the risk derived from the presence of pesticides in sediments must be assessed since some pesticides not detected at concerning levels in water, may pose a moderate/high risk in the sediments. Graphical abstract: Image 1 Highlights: Twenty-four of 69 pesticides were detected in sediments from Ebro River Delta. Bentazone and cypermethrin exhibited high levels and detection frequencies. Alfacs bay presented higher pesticide contamination than the Fangar bay. Detected pesticides may pose a moderate/high risk to sediment-dwelling organisms. Co-occurrence of pesticides may pose a high risk in 13 of 14 investigated locations.